Modulation of Cortical Inhibitory Circuits after Cathodal Transcranial Direct Current Stimulation over the Primary Motor Cortex - Sasaki, Ryoki; Miyaguchi, Shota; Kotan, Shinichi; Kojima, Sho; Kirimoto, Hikari; Onishi, Hideaki (Frontiers in Human Neuroscience, 2016)
Abstract Here we aimed to evaluate whether cathodal transcranial direct current stimulation (tDCS) over the primary motor cortex (M1) and primary somatosensory cortex (S1) can modulate cortical inhibitory circuits. Sixteen healthy subjects participated in this study. Cathodal tDCS was positioned over the left M1 (M1 cathodal) or left S1 (S1 cathodal) with an intensity of 1 mA for 10 min. Sham tDCS was applied for 10 min over the left M1 (sham). Motor evoked potentials (MEPs) elicited by transcranial magnetic stimulation (TMS) were recorded from the right abductor pollicis brevis muscle before the intervention (pre) and 10 and 30 min after the intervention (post 1 and post 2, respectively). Cortical inhibitory circuits were evaluated using short-interval intracortical inhibition (SICI) and short-latency afferent inhibition (SAI). M1 cathodal decreased single-pulse MEP amplitudes at post 1 and decreased SAI at post 1 and post 2; however, SICI did not exhibit any change. S1 cathodal and sham did not show any changes in MEP amplitudes at any of the three time points. These results demonstrated that cathodal tDCS over the M1 not only decreases the M1 excitability but also affects the cortical inhibitory circuits related to SAI.